The effect of a webquest reading lesson on learner autonomy in an efl classroom in Viet Nam : - Nguyen, Thi Thanh Mai (Trường Đại học Cần Thơ, 2010)
This study was conducted with a descriptive approach to determine if the webquest could promote academic autonomy and to investigate student's attiudes about the webquest in English as foreign language.